2017
DOI: 10.18869/acadpub.ibj.21.5.303
|View full text |Cite
|
Sign up to set email alerts
|

Expression Study and Clinical Correlations of MYC and CCAT2 in Breast Cancer Patients

Abstract: Background:Colon cancer-associated transcript 2 (CCAT2) is a newly recognized lncRNA transcribed from the 8q24 genomic region. It functions as an oncogene in various types of cancers including breast cancer, in which it affects Wnt/β-catenin pathway. Previous studies have shown a putative interaction between this lncRNA and MYC proto-oncogene.Methods:In the current study, we evaluated the expression of CCAT2 in breast cancer tissues with regards to the expression of its target MYC. In addition, we assessed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Wnt/β-catenin signaling can regulate a variety of developmental events, including proliferation and migration (40). In addition, it has been reported that lncRNA CCAT2 affects glioma, breast cancer and other tumors by regulating the Wnt/β-catenin pathway (35)(36)(37). TCF7L2 is an effector of the Wnt/E-catenin signaling pathway (41).…”
Section: Ccat2 Regulates Tcf7l2 Expression By Binding To Mir-217mentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt/β-catenin signaling can regulate a variety of developmental events, including proliferation and migration (40). In addition, it has been reported that lncRNA CCAT2 affects glioma, breast cancer and other tumors by regulating the Wnt/β-catenin pathway (35)(36)(37). TCF7L2 is an effector of the Wnt/E-catenin signaling pathway (41).…”
Section: Ccat2 Regulates Tcf7l2 Expression By Binding To Mir-217mentioning
confidence: 99%
“…It has also been reported that by activating the Wnt/β-catenin signaling pathway, lncRNA CCAT2 affects oral squamous cell carcinoma, ovarian cancer and renal cell carcinoma (33), as well as non-small cell lung cancer, breast cancer, esophageal cancer and glioma (15,17,(33)(34)(35)(36)(37). However, to the best of our knowledge, no studies have previously examined the relationship between CCAT2 and the Wnt/β-catenin signaling pathway in PCa, and its potential regulatory mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, they affect telomere biology, chromatin dynamics, genome structure organization [7], DNA repair [8] and tissue homeostasis [9]. They also participate in tumorigenesis process via different mechanisms, such as transcription repression [10], induction of epithelial-mesenchymal transition (EMT) [11], inhibition of tumor suppressors expression [12,13], over-expression of certain oncogenes [14,15], regulation of tumor-associated signal ing pathways [16] as well as modulation of tumor microenvironment [17]. Recently, a handful of lncRNAs have been shown to regulate the MAPK pathway through modulation of the expression of different proteins within this pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Such effect has been associated with alterations in the expression of certain transcripts including long non-cod ing RNAs (lncRNAs) in a way that these lncRNAs have been suggested as skin cancer biomarkers which are secreted into the blood or urine via exosomes [10]. In general, lncRNAs comprise an important portion of human transcriptome with fundamental roles in virtually every aspect of cell physiology [11]; their aberrant expression has been associated with pathologic conditions such as cancer [12][13][14][15][16][17][18]. More specifically, VDRregulated lncRNAs has been shown to participate in imprinting, tumor suppression and invasion/ metastasis which implies their involvement in the protective effect of VDR signal ing against skin cancer [10].…”
Section: Introductionmentioning
confidence: 99%